A hierarchical vision-based localization of rotor unmanned aerial vehicles for autonomous landing. (September 2018) - Yuan, Haiwen; Xiao, Changshi; Xiu, Supu; Zhan, Wenqiang; Ye, Zhenyi; Zhang, Fan; Zhou, Chunhui; Wen, Yuanqiao; Li, Qiliang
The vision-based localization of rotor unmanned aerial vehicles for autonomous landing is challenging because of the limited detection range. In this article, to extend the vision detection and measurement range, a hierarchical vision-based localization method is proposed for unmanned aerial vehicle autonomous landing. In such a hierarchical framework, the landing is defined into three phases: "Approaching, ""Adjustment, " and "Touchdown, " in which visual artificial features at different scales can be detected from the designed object pattern for unmanned aerial vehicle pose recovery. The corresponding feature detection and pose estimation algorithms are also presented. In the end, typical simulation and field experiments have been carried out to illustrate the proposed method. The results show that our hierarchical vision-based localization has the ability to a consecutive unmanned aerial vehicle localization in a wider working range from far to near, which is significant for autonomous landing.